Arteriovenous fistulas in the craniocervical junction region: With vs. without spinal arterial feeders - Song, Zihao; Ma, Yongjie; Wang, Yinqing; He, Chuan; Li, Guilin; Zhang, Peng; Hong, Tao; Sun, Liyong; Hu, Peng; Ye, Ming; Zhang, Hongqi (Frontiers in Surgery, 2023)
Objective Arteriovenous fistulas (AVFs) in the craniocervical junction (CCJ) region are a rare occurrence with special clinical manifestations. This study retrospectively reviewed patients with CCJ AVFs treated at our neurosurgical center, aiming to enhance the understanding of CCJ AVFs. Methods A total of 113 patients with CCJ AVFs treated at our neurosurgical center between January 2013 and December 2020 were enrolled. They were grouped as patients with CCJ AVFs with spinal arterial feeders (n = 20) and patients with CCJ AVF without spinal arterial feeders (n = 93). Clinical presentation, angiographic characteristics, intraoperative findings, and treatment outcomes were analyzed. Results The patients’ median age was 55 years (IQR 47.5–62 years). The proportion of males in the group without spinal arterial feeders was significantly higher (p = 0.001). Subarachnoid hemorrhage (SAH) was the most common clinical presentation, especially in the group with spinal arterial feeders (p < 0.001). There were significant differences in AVF type, fistula location, and direction of the venous drainage between the two groups (p < 0.001). Intervention embolization combined with microsurgery was more common in treating AVFs with spinal arterial feeders (p = 0.006). Spinal arterial feeders did not affect the outcome (p = 0.275). Conclusions SAH was the most common presentation of CCJ AVFs in this study. Microsurgery and interventional embolization were optional treatment strategies. The angioarchitecture of CCJ AVFs was essential for selecting treatment strategies.